Financial burden of complications following lung resection: a scoping review protocol - Laurence Weinberg; Stephen Barnett; Jordan Berman; Ariane Flinkier; Fabien Chu; Hugh Slifirski; Rebecca Caragata (BMJ Open)
Introduction Global healthcare expenditures are rising, driven largely by increased spending in both high- and low-income countries with hospitalisation as a primary contributor. Respiratory diseases, particularly lung cancer, pose significant public health and economic challenges with thoracic surgery as the standard curative treatment. Complications post resection, such as arrhythmias, infections and respiratory failure, result in substantial healthcare costs and resource demands. Although studies have explored the economic impact of surgeries, there is a limited comprehensive analysis of the financial burden of postoperative complications after lung resection surgery. To address this gap, this scoping review aims to map existing literature on lung resection complications and associated costs, providing insights for future research and healthcare policy.Methods and analysis This scoping review will be conducting according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Reviews standards. Eligible peer-reviewed articles and grey literature will be identified across Medical Literature Analysis and Retrieval System Online, Excerpta Medica Database and Cochrane Central Register of Controlled Trials. Cost data will be converted into US dollars as per the Federal Reserve Bank of St Louis and adjusted for inflation as per the US Bureau of Labor Statistics Consumer Price Index inflation calculator.Ethics and dissemination Ethics approval was not required. The results will be communicated through established professional networks, conference presentations and publication in peer-reviewed journals.